A sheet structured MOF magnet: Poly[(1, 10-phenanthroline)tetrakis(imidazolato)diiron(II)]. (29th March 2016) - Storr, Tim; Thompson, John R.; Patrick, Brian O.; Reiff, William M.; Storr, Alan; Thompson, Robert C.
Graphical abstract: Characterization of a new iron-containing sheet-structured metal organic framework is described that undergoes a magnetic phase transition to long-range order at ca. 7 K. Abstract: We report the synthesis and structural and magnetic characterization of poly[(1, 10-phenanthroline)tetrakis(imidazolato)diiron(II)], [Fe2 (imid)4 (phen)] x, 1 . The extended structure of1 is that of a metal organic framework (MOF) involving double layer sheets (bilayers) of alternating tetrahedral and octahedral irons singly bridged by imidazolate ligands. The octahedral iron centers are each additionally coordinated by phenanthroline ligands. Mössbauer spectroscopy confirms the presence of octahedral and tetrahedral metal centers. A combination of DC susceptibility, ZFCM and Mossbauer studies reveals a magnetic phase transition to long-range order at ∼7 K in1 . Magnetic hysteresis is observed at low temperatures, with coersive fields of approximately 360 and 650 G and remnant magnetizations of approximately 450 and 720 cm 3  G mol −1 at 5 and 2.5 K respectively.